Withholding Consent to Conjugal Relations within Child Marriages in Colonial India: Rukhmabai's Fight. (February 2020) - Sharma, Kanika
Abstract : Married at the age of eleven, Rukhmabai refused to go and live with her husband who had filed a suit for restitution of conjugal rights against her in 1884. This paper analyses the transplantation of the notion of restitution of conjugal rights into Hindu personal law in India at a time when child marriage was rife and there was no minimum age of marriage. Within this context Rukhmabai's case symbolises an important interjection in its attempt to posit lack of consent to an infant marriage as a defence against suits for restitution of conjugal rights. This marked a shift from female consent being understood as a question of physical maturity alone, to a claim of intelligent consent and the capacity to withhold such consent within an unconsummated marriage arranged in the girl's infancy. While analysing these notions of consent within colonial law the paper also closely scrutinises Rukhmabai's public writings to recover one of the earliest published Indian female views on the need for marital consent.